Discovering Plant Stress: Current trends and future perspectives in Plant-Microbe Interactions: Plant microbes’ interaction - Alsulami, Nadiah (Journal of King Abdulaziz University: Science, 2024)
Many biotic and abiotic factors can cause stress in plants, posing a major problem for agricultural yields, environmental health and food security globally. Plant stress can be caused by a variety of factors, including drought, high temperatures, disease and environmental changes. Adverse outcomes include developmental delay, decreased yield and diminished quality, as well as increased plant susceptibility to pests and diseases. Traditional breeding methods, advanced biotechnology treatments, cultural practices and biochemical interventions are all used to reduce the effects of the disease. In the future, plant stress management will focus on the utilization of climate-smart agriculture, precision agriculture and cooperative studies, policies and industries. Understanding and effectively managing plant stress will help us achieve sustainable agriculture, improve food security and protect our delicate ecosystems. Examining the complex world of plant stress in this in-depth study, we examine its various causes, its negative consequences and the approaches currently used to minimize them.